2010
DOI: 10.1002/jbm.b.31663
|View full text |Cite
|
Sign up to set email alerts
|

A novel gelatin sponge for accelerated hemostasis

Abstract: To more effectively manage the substantial bleeding encountered during surgical procedures in oto-rhino-laryngology, we developed a novel hemostatic sponge made of pharmaceutical grade, chemically cross-linked gelatin. The sponge is characterized by a high pore density, reduced ligaments, and a high nanoscale roughness of lamella surfaces in the matrix. In vitro blood uptake assays revealed a very rapid absorption of human blood, which was two to three times faster than that measured with comparative hemostypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 41 publications
0
60
0
Order By: Relevance
“…This was higher than the pore sizes found for freeze-dried collagen sponges (Fig. 5C) or for gelatine sponges (Hajosch et al 2010;Barbetta et al 2010). One of the most important criteria of surgical sponges is the absorption time (ta) of aqueous liquids.…”
Section: Resultsmentioning
confidence: 64%
“…This was higher than the pore sizes found for freeze-dried collagen sponges (Fig. 5C) or for gelatine sponges (Hajosch et al 2010;Barbetta et al 2010). One of the most important criteria of surgical sponges is the absorption time (ta) of aqueous liquids.…”
Section: Resultsmentioning
confidence: 64%
“…Although we found that OCP has superior osteoconductivity compared to other calcium phosphate materials [19], OCP lacks moldability and has been previously tested in combination with various natural polymers, such as collagen, gelatin, and alginate [13]. Gelatin is a material that has long been used safely and effectively as a biomaterial for medical use [33][34][35]. Moreover, our previous study confirmed that osteoblastic stromal cells attach well to Page 11 of 25 A c c e p t e d M a n u s c r i p t 11 OCP/Gel composite disks [30].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Gelfoam is readily designed to the shape and size as surgeons need. Gelfoam has been shown that it has a good hemostatic effect comparable to that of other packing materials [11]. Its surface essentially acts in the intrinsic pathway causing contact activation involving platelets and therefore it has hemostatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Gelfoam is gradually absorbed by phagocytosis and usually absorbed in approximately from 4 to 6 weeks [15]. Several trials have suggested that Gelfoam are biocompatible [11] and, in addition, Gelfoam packing has been long used in surgery of chronic otitis media without any complications. Some human studies suggest that absorbable gelatin film may predispose toward the formation of granulation tissue [16,17], whereas others suggest the opposite [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation